Improving Students Listening Skill by Using English Song at the 8thgrade Students of Islamic Junior High School of Hasyim Asy’ari Batu - Ellyas Emasari (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: The aim of this research is to describe how English song can improve the listening comprehension ability of MTS Hasyim Asyari Batu. The research problem of the study is “How can English song improve students listening skill at the 8thgrade students of Islamic junior high school of MTs Hasyim Asyari Batu”? This study used CAR (Classroom Action Research). The researcher tought once a week and needs 90 minutes. The participants of this research were 30 students (14 males and 16 females. The researcher used four instruments; observation sheet, field notes, test of listening skill, and documentation.The finding of the study explained that Song really engaged students’ interest, so that students can easily improve their listening skill. It meant that using song in teaching and learning process really gave high impact for students. This fact is proven by the result of the test that students is highly improved their listening skill after treatment. Before implementing the song to improve their listening, their score were 53,4. Then, after the researcher implementing the song, the researcher found out that the result increased (85,6). Based on the findings of the study, using English songs seem like very essential to overcome their lg problems. The researcher expected that the result will help the English teacher who consider English song as the media in teaching learning process to increase students’ ability in listening skill.In conclusion, regarding to the post-test score at 8th grade students of Islamic Junior High School of Hasyim Asy’ari Batu, using English song improved the students listening skill. Therefore, English song can be a good recommendation to use as a media that will help students enhance listening skill.Keywords: Improving, Listening Skill, English Song